2019
DOI: 10.1021/acs.analchem.9b04189
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Targeting Ratiometric Fluorescent Probe for Carboxylesterase 2 Detection in Drug-Induced Acute Liver Injury

Abstract: Carboxylesterase 2 (CES2), an endoplasmic reticulum (ER) located phase I enzyme, plays a vital role in the metabolism of various endogenous and exogenous substances, and is regarded as an important target for the design of prodrugs. Unfortunately, superior highly selective ER targeting fluorescent probes for monitoring of CES2 are not currently available. Herein, we report an ER targeting CES2 selective and sensitive ratiometric fluorescent probe ERNB based on the ER localizing group p-toluenesulfonamide. ERNB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 44 publications
(50 reference statements)
1
44
0
Order By: Relevance
“…James and Ma et al. designed an endoplasmic reticulum (ER) targeting ratiometric fluorescent probe 15 which can sensitively detect carboxylesterase 2 (CES2) and has an excellent ER‐targeting ability (Figure c) . P‐toluenesulfonamide was introduced to achieve the ER‐targeting ability of probe 15.…”
Section: Classification and Functions Of Cesssupporting
confidence: 91%
“…James and Ma et al. designed an endoplasmic reticulum (ER) targeting ratiometric fluorescent probe 15 which can sensitively detect carboxylesterase 2 (CES2) and has an excellent ER‐targeting ability (Figure c) . P‐toluenesulfonamide was introduced to achieve the ER‐targeting ability of probe 15.…”
Section: Classification and Functions Of Cesssupporting
confidence: 91%
“…Indeed, genetic abnormalities and the aberrant inflammatory microenvironment of the liver respond to the induction of ER stress in macrophages of ALI. Abundant genetic studies have revealed primary aberrances in several ER homeostasis-associated genes, such as carboxylesterase 2, sirtuin 1, and interferon regulatory factor 3, in AKI patients [31][32][33]. Combined with preceding studies from our team, ARRB1 may be a potential ER homeostasis-associated gene.…”
Section: Discussionmentioning
confidence: 75%
“… 346/528 174 CES2A CES2A-F5 8.58 34.87 430/542 24 CES2A CES2A-F6 1.92 20.4 600/662 23 CES2A CES2A-F7 6.6 N.A. 548/605 175 CES2A CES2A-F8 3.48 0.027 414/560 162 CES2A CES2A-F9 4.33 280.2 373/540 176
Figure 1 Design strategy for constructing CES optical substrates and the representative optical substrates.
…”
Section: Optical Substrates For Phase I Drug-metabolizing Enzymesmentioning
confidence: 99%